Distortions on the Battle of Cachirí and the Reestablishment of the Viceroyal Regime of the New Granada (1816) - Pérez Pinzón, Luis Rubén (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Historical events such as the battle of Cachirí (1816)demostrate that there is no narrative or explicative unitybetween different generations that have studied the nationalhistory, nor among the social classes that promote discoursesbased on their different imaginaries. This article describesthe variation in explanations between official history,popular memory and monument heritage of the regionalelite, regarding the battle that defined the triumph of theexpeditionary army of the Reconquista. For this purpose, weanalyze historical discourses that characterize the officialversion of the events taken place, and contrast them with theregional and national historical representations. At the sametime as we highlight the silences and anachronisms of thesehistories and representations from the point of view of popularmemory. All of this leads to identifying the different nationaldistortions that coexist regarding one event (the battle ofCachirí) and one historical character (Custodio García Rovira)in the New Granada of 1816.